Scaffolding Strategies: Enhancing L2 Students’ Participation in Discussions about Academic Texts - Eklund Heinonen, Maria; Lennartson-Hokkanen, Ingrid (Journal of Academic Writing, 2015)
Widening participation in higher education (HE) in recent decades has brought new challenges for both teachers and students. One growing group of students are L2 students who often report a lack of confidence in expressing themselves verbally in academic settings. Systematically scaffolding students into developing not only written but also spoken academic discourse is therefore an increasingly important challenge. In Sweden, L2 students are offered a qualifying course in Swedish to enable them to meet HE entry requirements. This paper reports a study carried out on the academic writing module of this course. Course activities include writing a short paper and participating in a critical discussion of peer papers, from which our data was collected. The study has a socioculturally based framework which suggests that learning takes place through social interaction. The purpose is to identify scaffolding strategies by means of a qualitative, interactional analysis. The findings indicate that different types of strategies, such as open-ended, follow-up and multi-unit questions, can help students to deliver more substantial and elaborate answers. Other useful strategies are to create reflective spaces and to focus on students’ identities as academic writers to achieve inclusive and empowering learning situations.